PATRIOTISM AS THE MOST IMPORTANT VIRTUE OF HUMANITY (TAMADDUN NURI JURNALI, 2025)
This article sheds light on the essence of the concept of patriotism. To love one's homeland, one needs tolerance. Such tolerance prepares a person for true courage, and if necessary, to sacrifice one's life. Today, spirituality serves as the most effective and powerful weapon in educating all-round excellent internal affairs officers in the spirit of patriotism.